THE EFFECTIVENESS OF MAKE A MATCH TECHNIQUE FOR TEACHING WRITING DESCRIPTIVE TEXT TO THE SEVENTH GRADERS OF SMPN 1 KARANGBINANGUN LAMONGAN (RETAIN, 2013)
Writing is one of four basic skills of English that has to be mastered by the students. However, it is not easy as it seems. There are some stages to make a good writing. Therefore, some teachers introduced many aids or techniques of teaching to help their students easy to compose a good writing. One of the interesting techniques of teaching is make a match technique. This study focuses on the effectiveness of using make a match technique to teach writing descriptive text. The research question here is “Is there any significant difference in writing ability between the students who are taught writing descriptive using make a match technique and those  who are taught without using make a match  technique?” This technique is one of cooperative learning that is played in pairs. The students are put in 2 groups, A and B, each of the students of the group get one card. Group A brings the questions (topic) cards; while B group brings the answers (simple description) cards. When they are ready to start, the teacher asks them to face each other cards. After that, she rings the whistle as a sign that they have to find their matches as soon as possible. When they already found their matches, they can report it to the teacher and if they are right, the teacher asks them to compose longer paragraph well. The research design used in this study was experimental research with two groups; experimental and control groups. The subjects of this study were seventh graders of SMPN 1 Karangbinangun Lamongan. The data were got from the students’ writing score in pre test and post test. The students’ scores were collected to collect the data. From the data collected, the researcher used T test to calculate the students’ pre test and post test scores. Based on the calculation of T test, the t- value of post test in both group were lower than t table. Therefore it could be said that there was no significant difference between experimental and control groups in post test. Based on the result above, in can be concluded that the use of make a match technique can help the students to get higher score in writing descriptive text. But this technique is not effective enough to be applied in this school. It can be seen from both students’ result of pre test and post-test. Key words: make a match, descriptive text, writing